Long term prognostic value of myocardial viability and ischaemia during dobutamine stress echocardiography in patients with ischaemic cardiomyopathy undergoing coronary revascularisation. Issue 2 (6th April 2005) - Rizzello, V; Poldermans, D; Schinkel, A F L; Biagini, E; Boersma, E; Elhendy, A; Sozzi, F B; Maat, A; Crea, F; Roelandt, J R T C; Bax, J J
Abstract : Objective: To evaluate the relative merits of viability and ischaemia for prognosis after revascularisation. Methods: Low–high dose dobutamine stress echocardiography (DSE) was performed before revascularisation in 128 consecutive patients with ischaemic cardiomyopathy (mean (SD) left ventricular ejection fraction (LVEF) 31 (8)%). Viability (defined as contractile reserve (CR)) and ischaemia were assessed during low and high dose dobutamine infusion, respectively. Cardiac death was evaluated during a five year follow up. Clinical, angiographic, and echocardiographic data were analysed to identify predictors of events. Results: Univariable predictors of cardiac death were the presence of multivessel disease (hazard ratio (HR) 0.21, p < 0.001), baseline LVEF (HR 0.90, p < 0.0001), wall motion score index (WMSI) at rest (HR 4.02, p = 0.0006), low dose DSE (HR 7.01, p < 0.0001), peak dose DSE (HR 4.62, p < 0.0001), the extent of scar (HR 1.39, p < 0.0001), and the presence of CR in ⩾ 25% of dysfunctional segments (HR 0.34, p = 0.02). The best multivariable model to predict cardiac death included the presence of multivessel disease, WMSI at low dose DSE, and the presence of CR in ⩾ 25% of the severely dysfunctional segments (HR 9.62, p < 0.0001). Inclusion of ischaemia in the model did not provide additional predictive value. Conclusion: The findings of the present study illustrate that in patients with ischaemic cardiomyopathy, the extent of viability (CR) is a strong predictor of long term prognosis after revascularisation. Ischaemia did not add significantly in predicting outcome.